Antiviral potential of selenium complexes from Brassicaceae by inhibiting protein bond between MAP4 and the spike of SARS-CoV-2 - Ilmiyah, Silvi Z.; Fakurazi, Sharida; Endharti, Agustina T.; Permana, Sofy (Academic Association of Pharmaceutical Sciences from Antofagasta, 2024)
Context: Coronavirus disease 2019 (COVID-19), a highly contagious viral disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a worldwide pandemic. Selenium derived from the plants of the Brassicaceae family plays an important role in several biological functions, often as an antioxidant or antiviral. In particular, selenium can be used as an adjuvant in the treatment of various viral infections. Aims: To determine the potential drug, as well as the affinity and the bond energy associated with chemical interaction bonds between the complex selenium compounds from Brassicaceae as inhibitors of the SARS-CoV-2 spike protein and MAP4 through the use of in silico studies. Methods: The methods used in this study consisted of receptor and ligand data collection, ADMET analysis, molecular docking, and molecular dynamics. Results: The results of this study indicate that the selenium complex compounds have the potential to be used as a spike inhibitor drug for SARS-CoV-2, as they have passed the Lipinski test and showed promise in the pharmacokinetic analysis. The results of the bond docking show that several complex selenium compounds, such as ethaselen, selenomethionine, and selenocystine, have stronger binding affinity values than the controls. This is compared to the control MAP4, which yielded binding affinities of -6.1 kcal/mol and spike protein -7 kcal/mol, respectively. Controlled bisoxatin and estramustine are drugs with mechanisms targeted to MAP4 and spike protein, which are the usual standards used. Conclusions: The similarity of sites, the binding of several amino acid residues dominated by hydrogen bonds, and the result of molecular dynamic results for the selenium compound derived from Brassicaceae showed a stable bond to the spike protein and MAP4 with low fluctuation levels.